'All Museums Will Become Department Stores': The Development and Implications of Retailing at Museums and Heritage Sites. Issue 1 (12th December 2016) - Larkin, Jamie
Abstract : Museums and heritage sites have provided merchandise for visitors to purchase since their earliest incarnations as public attractions in the 18 th century. Despite this longevity scant academic research has been directed towards such activities. However, retailing – formalised in the emergence of the museum shop – offers insights into a range of issues, from cultural representation and education, to economic sustainability. This paper outlines the historical development of retailing at museums and heritage sites in the UK, before offering a summary of current issues, illustrated by a case study of contemporary retailing at Whitby Abbey. The paper demonstrates how commercial spaces have made, and continue to make, important contributions to visitors' cultural experiences and aims to frame this topic as a legitimate field of academic enquiry.